2012
DOI: 10.4081/cardiogenetics.2012.e6
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of In Silico and In Vitro Splicing Assays for Interpretation of Genomic Variants of Unknown Significance in Cardiomyopathies and Channelopathies

Abstract: The identification of molecular anomalies in patients with inherited arrhythmias or cardiomyopathies is a multi challenge due to: i) the number of genes involved; ii) the number of polymorphisms and the fact that most mutations are private; and iii) the variable degree of penetrance which complicates family segregation study. Consequently, a number of unclassified variants (UV) are found in patients’ DNA and some (outside the canonical GT/AG) may affect splicing. Mutational screening on the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…4 However, both splice acceptor mutations demonstrated intron inclusion as opposed to exon skipping. 10, 11 For the exon splice site mutation Glu542Gln, we demonstrated not only a splice-defective transcript, but also a full-length missense transcript that was not previously appreciated. 13 Confirmation of the splice products for each mutation also prevented misclassification of mutations in exon splice sites as missense, 8, 14, 15 with important implications for disease pathogenesis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…4 However, both splice acceptor mutations demonstrated intron inclusion as opposed to exon skipping. 10, 11 For the exon splice site mutation Glu542Gln, we demonstrated not only a splice-defective transcript, but also a full-length missense transcript that was not previously appreciated. 13 Confirmation of the splice products for each mutation also prevented misclassification of mutations in exon splice sites as missense, 8, 14, 15 with important implications for disease pathogenesis.…”
Section: Discussionmentioning
confidence: 64%
“…Correct predictions of whether and to what degree these mutations alter splicing has critical implications for disease mechanisms elicited by these mutations. Splice predictions by in silico models, in vitro splice reactions, 10 or sequencing of peripheral blood leukocyte mRNA 4, 11 may not accurately predict the consequences of a splice site mutation in the relevant tissue. 12 In this study, we confirmed altered splicing and generation of a PTC from myocardium of all HCM patients harboring MYBPC3 mutations in consensus splice sites.…”
Section: Discussionmentioning
confidence: 99%
“…Alamut is a licensed software package available from Interactive Biosoftware (). To determine the robustness of our in silico predictions, we compared the effect on the splicing process of 10 previously reported intron mutations verified by in vitro/in vivo assay [19,20,21,22,23,24] with the outcome of our Alamut analysis, and obtained similar results (Supplementary Table S1). The results obtained with this predictor software for the novel intron variants are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 87%
“…CYP11A1 exon 5 with 313 flanking intronic bases in intron 4 and 241 flanking intronic bases in intron 5 was PCR amplified from the patient genomic DNA (total product size: 714 bp). Wild-type (WT) and mutated polymerase chain reaction (PCR) products were inserted in the Nde I restriction site of the pTB minigene vector as previously reported ( 24 , 25 ). Transfection in HeLa cells, reverse transcription -PCR (RT-PCR) procedures and analysis have been previously described ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type (WT) and mutated polymerase chain reaction (PCR) products were inserted in the Nde I restriction site of the pTB minigene vector as previously reported ( 24 , 25 ). Transfection in HeLa cells, reverse transcription -PCR (RT-PCR) procedures and analysis have been previously described ( 24 , 25 ). Reverse transcription-PCR products were analyzed by agarose gel electrophoresis (2%) and Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%